222 Pharmacovigilance Analysis of Reports of Sexual Dysfunction Associated with Finasteride Use: Implications for the Post-Finasteride Syndrome. Issue 1 (1st April 2022) - Nguyen, D; Herzog, P; Cone, EB; Labban, M; Zorn, KC; Chughtai, B; Basaria, S; Elterman, DS; Trinh, Q; Bhojani, N
ABSTRACT: Introduction: Finasteride, a 5α-reductase inhibitor, is used in the management of androgenetic alopecia and benign prostatic hyperplasia (BPH). There is growing attention to the post-finasteride syndrome, a constellation of adverse events associated with finasteride use which include sexual dysfunction. Objective: To investigate reports of sexual dysfunction associated with finasteride. Methods: We conducted a pharmacovigilance study using VigiBase, the World Health Organization's international database of individual case safety reports. We used the reporting odds ratio (ROR). Sensitivity analyses stratified by indication (BPH and alopecia) and age (<45 and ≥45); compared finasteride signals to those of drugs with different mechanisms but similar indications (minoxidil for alopecia and tamsulosin for BPH); compared finasteride to a drug with a similar mechanism of action (dutasteride); and compared reports of sexual dysfunction before and after 2012. Results: We identified 7700 sexual dysfunction reports associated with finasteride. There was a disproportionality signal for sexual dysfunction associated with finasteride (ROR 50.3, 95% confidence interval (CI) 49.0-51.6). Patients under 45 (ROR 56.4, 95% CI 53.1-59.9) and alopecia patients (ROR 64.9, 95% CI 62.7-67.2) drove the signal. All sensitivity analyses met the threshold of signal significance. Results of primary and sensitivity analyses are presented in Tables 1 and 2. Conclusions: We detected disproportional signals of sexual dysfunction linked with finasteride use. Despite sexual dysfunction being more prevalent in older BPH patients, we detected larger signals of sexual dysfunction in young alopecia patients. Sensitivity analyses suggest that reports of sexual dysfunction linked with finasteride use may be confounded by indication and by stimulated reporting. However, confounding alone is unlikely to account for the totality of the signal observed in young patients with alopecia. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: QDT reports personal fees from Astellas, Bayer, Janssen, Insightec, and Intuitive Surgical, outside the submitted work. NB, DSE, and KCZ reports consulting fees from Procept Robotics, Olympus, and BSC. BC reports consulting fees from BSC, Olympus, Meditate, Ferring, and Urovant.